1997
DOI: 10.1210/jcem.82.12.4470
|View full text |Cite
|
Sign up to set email alerts
|

Human Estrogen Receptor β-Gene Structure, Chromosomal Localization, and Expression Pattern1

Abstract: The estrogen receptor (ER) is a ligand-activated transcription factor that mediates the effects of the steroid hormone 17 beta-estradiol, in both males and females. Since the isolation and cloning of ER, the consensus has been that only one such receptor exists. The finding of a second subtype of ER (ER beta) has caused considerable excitement amongst endocrinologists. In this article, we present data regarding the genomic structure and chromosomal localization of the human ER beta gene, demonstrating that two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(78 citation statements)
references
References 25 publications
0
67
0
6
Order By: Relevance
“…Synthetic compounds also regulate gene expression in prostate cancer cells through ER␤, which is the predominant ER subtype in those cells (18)(19)(20). Being dependent on agonistic ligands such as E2, ER directly binds to estrogen response elements (EREs) within genomic DNA to induce gene expression (classical pathway) (21).…”
mentioning
confidence: 99%
“…Synthetic compounds also regulate gene expression in prostate cancer cells through ER␤, which is the predominant ER subtype in those cells (18)(19)(20). Being dependent on agonistic ligands such as E2, ER directly binds to estrogen response elements (EREs) within genomic DNA to induce gene expression (classical pathway) (21).…”
mentioning
confidence: 99%
“…Many published studies since the discovery of ERβ in 1997 indicated that ERβ was distributed in the human tissues and more expressed in the normal colonic epithelium, suggesting that estrogens may play an important role in the growth of normal colonic mucosa [31,32]. In addition to the above estrogen β receptor considered the dominant receptor type in normal colonic tissue and its down-regulation may be linked to the progression of colorectal cancer [33].…”
Section: Discussionmentioning
confidence: 99%
“…Two years later ERβ was definitively identified as a 530 residue protein [138]. ERα and ERβ are the products of two genes belonging to different chromosomes (6q25.1 and 14q23-24.1 respectively) [139, 140]. Although only two ERs have been found in mammals, a third ER (ERγ) has been identified in fish species [141].…”
Section: Molecular Mechanismsmentioning
confidence: 99%